Evaluation of the level of tumor necrosis factor-alpha and lactate dehydrogenase in acute lymphoblastic leukemia patients - Raghad Yaarob Ahmed; Zainab Issam Al Hatem (Iraqi Journal of Hematology)
BACKGROUND: Acute lymphoblastic leukemia (ALL) is an abnormal clonal proliferation of early hemopoietic precursor cells in bone marrow (BM). There are certain cytokines like tumor necrosis factor alpha (TNF-α) which plays a crucial role in the development and progression of malignant process, and other enzymes like lactate dehydrogenase (LDH) which has prognostic value. OBJECTIVE: The aims of this study were to evaluate the level of serum TNF-α and LDH in ALL patients at diagnosis and post-induction chemotherapy. PATIENTS, MATERIALS, AND METHODS: This was an observational–analytical study, which was done in Ibn-Sina Teaching Hospital in the period between May 2023 and November 2023. It included 22 newly diagnosed patients with ALL. All patients underwent complete blood count, bone marrow examination, flowcytometry, serum TNF-α and LDH at diagnosis and post induction chemotherapy. RESULTS: In 22 patients with ALL, at diagnosis, the means of serum TNF-α (97.89 ± 52.945 ng/l), serum lactate dehydrogenase(1138.94 ± 430.10 IU/l), and percentage of blasts cells in BM (0.742 ± 0.181) in B-ALL. The means of serum TNF-α (165.33 ± 23.437 ng/l), serum lactate dehydrogenase (1633.33 ± 497.426 iu/l), and percentage of blasts cells in BM (0.816 ± 0.125) in T-ALL were statistically higher than those among the controls (s.TNF-a (18.09 ± 6.795 ng/l), s.LDH (142.59 ± 61.626 IU/l), and percentage of blasts cells in BM 0.0 ± 0.0) with P = 0.000 for all parameters mentioned, respectively. After induction phase chemotherapy in B-cell ALL , there were a significant reduction noted for serum TNF-α (29.26 ± 18.648 ng/l) and LDH levels (245.47 ± 154.592 IU/l) and a significant decrease in the percentage of blasts cells (0.07 ± 0.060).also in T-cell ALL there were a significant reduction noted for serum TNF-a (26.00 ± 11.135 ng/l) serum LDH (347.66 ± 160.300 IU/l) and percentage of blasts cells in bone marrow (0.06 ± 0.046). All of the postchemotherapy acute leukemia cases with lower TNF-α levels had complete remission (100%). CONCLUSIONS: There were significant increases in serum TNF-α and LDH in ALL patients at diagnosis; while after induction, there was a significant reduction in their levels. Complete remission from the disease was associated with lower levels of serum TNF-α in newly diagnosed patients.